2018
DOI: 10.1007/s00383-018-4361-y
|View full text |Cite
|
Sign up to set email alerts
|

Impact of simulation-based training on perceived provider confidence in acute multidisciplinary pediatric trauma resuscitation

Abstract: Purpose: Simulation-based training has the potential to improve team-based care. We hypothesized that implementation of an in situ multidisciplinary simulation-based training program would improve provider confidence in team-based management of severely injured pediatric trauma patients. Methods: An in situ multidisciplinary pediatric trauma simulation-based training program with structured debriefing was implemented at a free-standing children’s hospital. Trauma providers were anonymously surveyed one month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 24 publications
0
14
0
3
Order By: Relevance
“…Two thirds of respondents reported they could manage aggression at follow-up. Confidence in patient management has been shown to be maintained in a number of simulation studies [75,77,78,80] and even increased [81,82] up to 1 year post-training. This study supports and extends the findings of de la Fuente and Schoenfisch [83] who reported nurses' confidence in coping with patient aggression to be higher in post behaviour management training and maintained up to 1 month following the training.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Two thirds of respondents reported they could manage aggression at follow-up. Confidence in patient management has been shown to be maintained in a number of simulation studies [75,77,78,80] and even increased [81,82] up to 1 year post-training. This study supports and extends the findings of de la Fuente and Schoenfisch [83] who reported nurses' confidence in coping with patient aggression to be higher in post behaviour management training and maintained up to 1 month following the training.…”
Section: Discussionmentioning
confidence: 95%
“…Organisational culture may influence the delivery, uptake and effectiveness of simulation-based group training programmes. Whilst there is evidence that simulation may be the most effective format for teaching and practicing clinical skills [76,84,85], there is also evidence that institutional culture, with an emphasis on collaborative, interprofessional learning through simulation coupled with repeated exposure to clinical events, may increase confidence in managing clinical situations long term [82]. This concept is reinforced by this study where participants who had experienced clinical aggression post-training, reported increased perceived confidence at follow-up compared to immediately post-training.…”
Section: Discussionmentioning
confidence: 99%
“…Although dissemination strategies were most used in the included studies, capacity building and scale-up were most effective. A before and after study [ 9 ] investigated the effect of implementing a simulation-based training program on healthcare provider confidence in team-based management of severely injured pediatric trauma patients and found a positive response as the healthcare provider confidence on long-term exposure was improved. They used dissemination strategies in which healthcare providers underwent a 40-minute structured debriefing with trained debriefers after a training session.…”
Section: Discussionmentioning
confidence: 99%
“…Other published curriculums for this learner group are not as thorough as this curriculum. They tend to focus on either a single training gap such as trauma management [51] or delivering challenging news [52], focus on a single piece of the curriculum development process [53], or do not as thoroughly describe their process [51]. As a result, we believe our curriculum is the most generalizable and adaptable curriculum to date.…”
Section: Discussionmentioning
confidence: 99%